(untitled) (Journal of Informatics Education and Research, 2024)
India is a huge and culturally ranged country, with numerous languages, cultures, and traditions. This range creates both possibilities and issues for the fintech sector, which aims to make financial services easier and more readily available to the Indian populace. This research paper investigates the effect of linguistic and cultural diversity on fintech adoption in the Indian market. It explores how such features affect customer behavior, preferences, and attitudes regarding solutions offered by fintech. Recognizing these characteristics allows fintech companies to design strategies for resolving obstacles and gaining acceptance across India’s various geographic regions and populations.